Impact Area Determination of Pyroclastic Deposits in Lascar Volcano, Eruptive Process in the Year 1993 - Salinas-Silva, R (2012)
By means of multi-temporal analysis of satellite images and statistical algorithms, the amount of pyroclastic material deposited on Lascar volcano walls after the gravitational collapse of the eruptive column caused by the eruption that occurred on April the 19th and the 20th in 1993 was determined and quantified. For this analysis, scenes corresponding to Landsat 4 TM in 1989 and Landsat 7 ETM+ in 2001 were used. By careful selection methods such as combination of bands, unsupervised classification, and the Karhunen-Loève transform, detailed analysis of zones of change that correspond to pyroclastic deposits were made. This analysis was complemented with in situ data in order to correct and calibrate the satellite images to identify zones of 1993s eruption pyroclastic deposits. Using Kittler s and other thresholding algorithms, a search was performed for a proper threshold to binarize the images to determine the surface area covered by the eruptive process. Matlab™ software was used both for general programming and for digital image processing. © 2011 Springer Science+Business Media B.V.
Keywords: Remote sensing; Image processing; Thresholding; Binarization